2021
DOI: 10.1111/ele.13870
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the complexity of priority effects in multispecies communities

Abstract: The history of species immigration can dictate how species interact in local communities, thereby causing historical contingency in community assembly. Since immigration history is rarely known, these historical influences, or priority effects, pose a major challenge in predicting community assembly. Here, we provide a graph-based, non-parametric, theoretical framework for understanding the predictability of community assembly as affected by priority effects. To develop this framework, we first show that the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…Understanding how species assemble into communities is a central issue in community ecology (Fukami, 2015; Song et al ., 2021; Serván & Allesina, 2021). Community assembly is typically modeled as a sequence of invasions of species from a regional species pool into a local patch, where the success of each invasion may depend on both the environmental conditions as well as the local community itself (HilleRis-Lambers et al ., 2012; Barbier et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how species assemble into communities is a central issue in community ecology (Fukami, 2015; Song et al ., 2021; Serván & Allesina, 2021). Community assembly is typically modeled as a sequence of invasions of species from a regional species pool into a local patch, where the success of each invasion may depend on both the environmental conditions as well as the local community itself (HilleRis-Lambers et al ., 2012; Barbier et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the process of community assembly is closely related to its predictability(18, 35, 36), so we explored the association between microbial community assembly mechanisms in AS systems and the predictability of the corresponding taxa. By neutral community model (NCM) model fitting, we found that stochastic processes explained 63.3% of the microbial community variation in AS systems (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the demonstrated examples, we also expect that our metric should be particular useful in determining the relationship between species composition and ecosystem functioning (Grman et al ., 2018; Mori et al ., 2018) and stability (McGranahan et al ., 2018) because it explicitly takes species-association into account. When applied in the temporal context, the hypervolume-based beta diversity is also a measure of community change predictability (Song et al ., 2021; De Cáceres et al ., 2019): for example, in time-lag analysis, higher beta diversity indicates more random community composition changes over time while lower beta diversity indicates more directional changes (Jones et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%